Implementation of DOA Estimation System Based on HackRF One - Zihan Zhang; Wenjie Zhao; Yonghui Huang; Junshe An; Yan Zhu (International Journal of Antennas and Propagation)
In the practical direction of arrival (DOA) estimation applications, it is required that the multichannel signal acquisition equipment can synchronously collect the signals received by the array antenna. In addition, the signal phase relationships between channels are supposed to be stable. However, this kind of equipment is usually complex and expensive to manufacture. Since some SDR devices are reconfigurable and open source, this paper adopts HackRF Ones as the signal sampling devices to design the DOA estimation system. The clocks line is used to synchronize the clock frequencies between HackRF Ones. Besides, an external pulse is introduced to control the sampling devices to start sampling simultaneously. In this case, the stable phase difference between channels can be obtained. The experimental results show that the synchronization error between channels of the system is less than one sampling period. The system can be used to estimate the incident angles of single carrier signals or modulated signals. The RMS errors of the system when estimating one source and two sources are 1.94° and 2.85°, respectively.